A Review Of Backfilling At Black Mountain Mine - P. J. Kinver (The Southern African Institute of Mining and Metallurgy, 1988)
This paper deals with the development of backfilling methods and systems at the Broken Hill orebody of Black Mountain Mineral Development Company (Pty) Limited, at Aggeneys in the north-western Cape Province. Production started in 1979, being confined to large diameter blasthole stoping methods in the upper, steeply dipping areas of the orebody. This blasthole reserve is now depleted and the production tonnage, 100000 tons per month, is produced from eight cut and fill stopes in the flatter dipping areas of the orebody. The fill methods of the blasthole stoping area evolved prior to the pillar extraction are briefly discussed together with the resulting experiences gained that enabled virtually 100% extraction to be achieved. The original cut and fill mining used costly hydraulic cemented fill; this was replaced partly by unconsolidated river sand and later by dune sand which occurs in abundance. The paper describes the planning, research work and commissioning of a cycloning plant that now enables dune sand to be used successfully as an unconsolidated hydraulic fill. The development of drainage, placement and control methods are also reviewed.